1997
DOI: 10.1111/j.1095-8312.1997.tb01777.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological morphology of lacustrine threespine stickleback Gasterosteus aculeatus L. (Gasterosteidae) body shape

Abstract: Threespine sticklebacks, small fish with a circumglobal distribution in coastal marine and freshwater of the northern hemisphere, present a remarkable scope of variation in body and fin shape among populations. The repeated evolution of divergent body shapes in a radiation of stickleback from Cook Inlet, Alaska suggests that diversification has proceeded by extensive parallel selection. To explore this hypothesis, hydromechanical equations of fish propulsion and descriptions of stickleback foraging and anti-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

37
474
4
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(520 citation statements)
references
References 246 publications
37
474
4
1
Order By: Relevance
“…Past studies have shown that predation risk and diet as separate factors can affect the body shape of organisms (Brö nmark & Miner 1992;Robinson & Wilson 1995), but there is an increasing interest in how these two factors might interact (Walker 1997;Vamosi & Schluter 2002;Chipps et al 2004). However, these studies have been performed on fish caught in different habitats, which precludes any detailed analysis of the separate mechanisms behind the morphological adaptations and the relationship between them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past studies have shown that predation risk and diet as separate factors can affect the body shape of organisms (Brö nmark & Miner 1992;Robinson & Wilson 1995), but there is an increasing interest in how these two factors might interact (Walker 1997;Vamosi & Schluter 2002;Chipps et al 2004). However, these studies have been performed on fish caught in different habitats, which precludes any detailed analysis of the separate mechanisms behind the morphological adaptations and the relationship between them.…”
Section: Discussionmentioning
confidence: 99%
“…Since predators induce both morphological shifts and behavioural changes that result in diet shifts (Turner & Mittelbach 1990;Tollrian & Harvell 1999), the effect of predator-induced morphological changes and dietinduced changes may depend on each other (Caldwell 1986;Walker 1997;Vamosi & Schluter 2002;Chipps et al 2004). For example, consider a system where the presence of a predator chemically induces a change in body shape in a prey, and at the same time causes a shift in prey habitat use because of predator avoidance behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…The potential for such confounding can be examined post hoc by using matrix correlation analysis to assess the independence of spatial and genetic patterns in phenotypic data across populations (for examples of this approach, see [70,71]). Where population relationships are known in advance, this problem may be avoidable by sampling an appropriate set of populations for which predicted patterns based on relatedness and selection are not the same [26,110].…”
Section: Analysis Of Patterns Across Populations Within Speciesmentioning
confidence: 99%
“…Whether the link between predators and increased body depth is direct or indirect is still debated, as it may be the consequence of altered behaviour [34] such as reduced activity in the presence of predators [35] or differential habitat use and diet [36]. The effect of predator pressure on shape may even reflect a functional trade-off between foraging performance in different habitats and predator avoidance [37].…”
Section: Introductionmentioning
confidence: 99%